2006
DOI: 10.1007/s10439-006-9231-4
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Objective Response Detectors (MORD): Statistical Tools for Multichannel EEG Analysis During Rhythmic Stimulation

Abstract: The presence of cerebral evoked responses can be tested by using objective response detectors. They are statistical tests that provide a threshold above which responses can be assumed to have occurred. The detection power depends on the signal-to-noise ratio (SNR) of the response and the amount of data available. However, the correlation within the background noise could also affect the power of such detectors. For a fixed SNR, the detection can only be improved at the expense of using a longer stretch of sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 11 publications
1
11
0
6
Order By: Relevance
“…If several harmonics are expected to be present in the signal, they may be assessed conjointly [15]. Sensitivity can be improved if the data of several electrodes are available [16]. As always with statistics, stating the hypothesis very precisely beforehand allows for choosing the most adequate test.…”
Section: Objective Response Detection and Comparison To Normal Valuesmentioning
confidence: 99%
“…If several harmonics are expected to be present in the signal, they may be assessed conjointly [15]. Sensitivity can be improved if the data of several electrodes are available [16]. As always with statistics, stating the hypothesis very precisely beforehand allows for choosing the most adequate test.…”
Section: Objective Response Detection and Comparison To Normal Valuesmentioning
confidence: 99%
“…Moreover, the investigation of multivariate extensions of these techniques would allow obtaining detectors with higher performances for identification of visual (Felix et al, 2007) or somatosensory (Melges et al, 2012b) stimulation response. Finally, the frequencies with best detection rates were the same reported by Infantosi et al (2006) and Melges et al (2012b), which used uni and multivariate ORD.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that the mean phase angle is uniformly distributed between 0 and 2, it can be showed, in a similar way to the performed to the CSM, that the asymptotical critical value for the MCSM can be expressed by (Felix et al, 2007) …”
Section: Multiple Component Synchrony Measure (Mcsm)mentioning
confidence: 98%
“…This result was observed for different values of M epochs (100, 200, 400, 800) used in the calculation of the estimates. A comparison between the two techniques applied to the EEG during intermittent photic stimulation (Felix et al, 2007) has also resulted in higher detection percentages for the MC over the MCSM. By means of simulation, it was observed that the presence of noise correlated with the responses degrades the detection rates (Felix et al, 2007).…”
Section: Multivariate Ord (Mord) Techniquesmentioning
confidence: 99%
See 1 more Smart Citation